Navigating transparency : The interplay of ESG disclosure and voluntary earnings guidance - Agapova, Anna; King, Tatiana; Ranta, Mikko (Elsevier, 2024)
In accordance with stakeholders' theory and the reputation-building hypothesis, environmental, social and governance (ESG) disclosure and voluntary earnings guidance are important ways of enhancing a firm's transparency. Using data of U.S. publicly listed companies from 2002 to 2021, we find that the level of ESG disclosure (measured with Bloomberg and machine learning (ML) ESG disclosure scores) is associated with increased information asymmetry. A subsequent examination reveals a positive relation between ESG disclosure levels and earnings guidance. The result holds in a robustness test of quasi-exogenous event of the initiation of the Bloomberg ESG disclosure coverage of firms. We deduce that firms are using voluntary earnings guidance to counterbalance the adverse impact of ESG disclosure on transparency. The study provides new insights on the factors that determine voluntary earnings guidance through firms' involvement in ESG disclosure.
Keywords: ESG; earnings guidance; ESG disclosure; corporate social responsibility; information asymmetry; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|